(3x-2)(5x+4)=0

Simple and best practice solution for (3x-2)(5x+4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-2)(5x+4)=0 equation:


Simplifying
(3x + -2)(5x + 4) = 0

Reorder the terms:
(-2 + 3x)(5x + 4) = 0

Reorder the terms:
(-2 + 3x)(4 + 5x) = 0

Multiply (-2 + 3x) * (4 + 5x)
(-2(4 + 5x) + 3x * (4 + 5x)) = 0
((4 * -2 + 5x * -2) + 3x * (4 + 5x)) = 0
((-8 + -10x) + 3x * (4 + 5x)) = 0
(-8 + -10x + (4 * 3x + 5x * 3x)) = 0
(-8 + -10x + (12x + 15x2)) = 0

Combine like terms: -10x + 12x = 2x
(-8 + 2x + 15x2) = 0

Solving
-8 + 2x + 15x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-4 + -5x)(2 + -3x) = 0

Subproblem 1

Set the factor '(-4 + -5x)' equal to zero and attempt to solve: Simplifying -4 + -5x = 0 Solving -4 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -5x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -5x = 0 + 4 -5x = 0 + 4 Combine like terms: 0 + 4 = 4 -5x = 4 Divide each side by '-5'. x = -0.8 Simplifying x = -0.8

Subproblem 2

Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667

Solution

x = {-0.8, 0.6666666667}

See similar equations:

| 272-37x=-45x | | 9x+3=4x+9 | | x^2-10x=37 | | (2x^2+3x-6)+(x^2-18x+6)= | | 4x-6=-14 | | 2x^4+16x^2=4 | | 3x-8=20x+26 | | x^2+14x=-10 | | 2((42-3x)+x)=60 | | 3x^2-10x+8= | | x+(x-1)+(x-2)+(x-3)=-14 | | x^2+6x=11 | | 4x-158=36 | | l+2.5=14 | | 3x^2+8x+4= | | x+42-3x=60 | | s^2+5s+6=0 | | 3m+6m+6=24 | | 13x-23-45=-7x+12 | | 25y=34y-252 | | 7n^2+9n+2= | | -2(2x+7)=1 | | 5x^2-2x-7= | | 10x-12+10=18-20 | | 2y^2-9y-5= | | 3x^2+30x-18= | | x+4=-6x+18 | | X^2-4c-30=0 | | 19+2x-13=10-20 | | 25x^2-7x+9=-37x | | 3x-12=27 | | 4x+5-2x+3=-8 |

Equations solver categories